Vasa, Piwi, and Pl10 Expression during Sexual Maturation and Asexual Reproduction in the Annelid Pristina longiseta - Roman P. Kostyuchenko; Natalia P. Smirnova (Journal of Developmental Biology, 2023)
Naidids are tiny, transparent freshwater oligochaetes, which are well known for their ability to propagate asexually. Despite the fact that sexually mature individuals and cocoons with embryos are sometimes found in nature, in long-period laboratory cultures, worms reproduce agametically only. In this paper, we showed, for the first time, the expression of Vasa, Piwi, and Pl10 homologs in mature Pristina longiseta worms with well-developed reproductive system structures and germ cells. Although the animals have been propagated asexually by paratomic fission for over 20 years in our lab, some individuals become sexualized under standard conditions for our laboratory culture and demonstrate various stages of maturation. The fully matured animals developed a complete set of sexual apparatus including spermatheca, atrium, seminal vesicles, and ovisac. They also had a clitellum and were able to form cocoons. The cues for the initiation of sexual maturation are still unknown for P. longiseta; nevertheless, our data suggest that the laboratory strain of P. longiseta maintains the ability to become fully sexually mature and to establish germline products even after a long period of agametic reproduction. On the other hand, many of the sexualized worms formed a fission zone and continued to reproduce asexually. Thus, in this species, the processes of asexual reproduction and sexual maturation do not preclude each other, and Vasa, Piwi, and Pl10 homologs are expressed in both somatic and germline tissue including the posterior growth zone, fission zone, nervous system, germline cells, and gametes.